Effect of various soil amendments on soil pH and exchangeable Ca at different depths in the identification of a suitable liming material for tannia (Xanthosoma sagittifolium L. Schott) in an Ultisol, Kerala, India - K. Susan John; R. T. Remya Raj (JOURNAL OF ROOT CROPS, 2024)
Tannia (Xanthosoma sagittifolium L. Schott) is an important tropical tuber crop coming under the group of aroids. It is usually grown as intercrop in plantations and fetches good remuneration. When this crop is grown in the acid laterite soils (Ultisols), widespread occurrence of Mg deficiency was very common resulting in the complete devastation of the crop. The reason attributed was the acidity due to excess Al3+ions in the subsoil layers which causes the decay of roots and hence adversely affecting the absorption of water and nutrients. This crop being an indicator plant for Mg deficiency, the symptom is manifested as interveinal chlorosis coupled with drying of the whole plant. The present study was undertaken to screen a better soil amendment to tackle the problem of subsoil acidity induced multi nutrient disorder in tannia. The present study was done using five liming materials viz., calcite, dolomite, gypsum, calcium silicate and calcium oxalate at quantities ranging from 50-1000g both under controlled condition in lysimeter and in field. After application of treatments, soil samples drawn continuously for 6-7 months from four different depths viz., 0-15, 15-30, 30-45 and 45-60 cm were analysed for pH, CEC and exchangeable Ca. The data generated were statistically analysed for the independent and interaction effect of treatments (liming materials, rate of application, depth of sampling and interval after application) and results on the mean effect, changes over initial and at the end of 6-7 months of application with respect pH and exchangeable Ca for the above treatments were described. The results from both situations revealed that, calcite, dolomite and gypsum were equally effective. Among the three, dolomite being a source of both Ca and Mg, even at lower quantities as 250 g was found better in enhancing both pH (1.54 units over initial) and exchangeable Ca (1.559 cmol (+) kg soil-1 over initial) to the maximum extent especially at lower depths up to 60 cm to a period of 4-5 months after application.